PERCEPTIONS OF DEAF STUDENTS ABOUT THE SCHOOLING PROCESS IN A PUBLIC SCHOOL AND IN A BILINGUAL SCHOOL - Prates, Claudia Aparecida [UNESP]; Tescaro Santos Lino, Carla Cristine [UNESP] (Fundacao Univ Tocantins, 2021)
This study investigated the perceptions of deaf students and educational approaches in the schooling process from basic education to university. The research participants were four deaf students: two from a bilingual basic education school and two from ordinary school. The study is qualitative / descriptive. In the data collection, unstructured, filmed interviews were used and, for transcription, the professional interpreter of Libras translated Libras into Portuguese. Content Analysis allowed us data for categories. This research evidenced the need to overcome challenges, such as the construction of clearer meanings about methodologies for the deaf student who builds all his cognitive experience through the visuo-espatial language and imagery contents. In this sense, the bilingual school considers these specificities for the cognitive development of the deaf student, while the common one needs to rethink its pedagogical practices to guarantee inclusion.
Keywords: Bilingualism; Deaf; Inclusion